Influence of Product Quality, Promotion and Design on Purchase Decision of Scooter Matic Vario - Oscarius Yudhi Ari Wijaya (International Journal of Economics Development Research (IJEDR), 2023)
This research aims to know the influence between product quality, promotion and product design on purchase decision of Scootermatic Vario on CV. Picture Honda Nusantara, South Sumatra. The population in this study was 572 people buying scooters matic Vario on CV. Image Honda Archipelago South Sumatra And sample selected as much as 100 respondents using technique accidental sampling. Data collection techniques in this study using questionnaire techniques, interviews, observation and literature study. Obtained data analyzed quantitatively using analytical tools in the form of validity tests, reliability test, multiple linear regression and hypothesis testing with the t-test and f-test using the Statistical Package for the Social Sciences (SPSS) program. From the results of the statistical analysis are known to have a positive and significant effect between quality product, promotions and design to decision purchases scootermatic Vario. The coefficient of determination for variables independent donate as large 36.2% for decision purchases scootermatic Vario on CV. Citra Honda Nusantara South Sumatra while 63.8% influenced by other factors. Suggestions that can be conveyed are the company must improve competitiveness by improving product quality, promotion and design to be able to compete with its competitors in the automotive industry.